2022
DOI: 10.1002/pits.22775
|View full text |Cite
|
Sign up to set email alerts
|

School‐based racial microaggressions and depression among Indigenous young adults

Abstract: Previous research on the risk factors for the development of mental health disorders among Indigenous Peoples in the United States suggest that experiencing prejudice is correlated with the development of psychopathology. However, the relation between school‐based prejudice, including microaggressions, and the development of depression remains unexamined. As such, the current study is an exploratory analysis among a small sample (N = 47) of age 18–25 Indigenous young adults from the American Northwest examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…Students as young as those in middle school have expressed awareness of microaggressions from peers and teachers (Banks et al, 2020). Holter et al (2022) studied the relation between school-based microaggressions and depression in Indigenous adolescents; microaggressions can emerge in peer-to-peer conversations, teacher or faculty conversations, textbooks, and other educational materials. These everyday statements and images result in marginalized students feeling unsafe and unwelcome (Holter et al, 2022).…”
Section: Understanding the Impacts Of Microaggressions And Microaffir...mentioning
confidence: 99%
See 3 more Smart Citations
“…Students as young as those in middle school have expressed awareness of microaggressions from peers and teachers (Banks et al, 2020). Holter et al (2022) studied the relation between school-based microaggressions and depression in Indigenous adolescents; microaggressions can emerge in peer-to-peer conversations, teacher or faculty conversations, textbooks, and other educational materials. These everyday statements and images result in marginalized students feeling unsafe and unwelcome (Holter et al, 2022).…”
Section: Understanding the Impacts Of Microaggressions And Microaffir...mentioning
confidence: 99%
“…Holter et al (2022) studied the relation between school-based microaggressions and depression in Indigenous adolescents; microaggressions can emerge in peer-to-peer conversations, teacher or faculty conversations, textbooks, and other educational materials. These everyday statements and images result in marginalized students feeling unsafe and unwelcome (Holter et al, 2022). The way a student perceives their school environment can have a direct impact on academic achievement, classroom behavior, and social interactions (Banks et al, 2020; Steketee et al, 2021).…”
Section: Understanding the Impacts Of Microaggressions And Microaffir...mentioning
confidence: 99%
See 2 more Smart Citations
“…One experience that is nearly ubiquitous in the experience that NA students face on campus is the presence of microaggressions or discrimination (Bradford, 2021;Fish et al, 2017;Mcmillan, 2020;O'Keefe & Greenfield, 2019). Microaggressions and discrimination can lead to many negative outcomes for NA students, including depression (Holter, 2020) and substance abuse (Fish et al, 2017;Greenfield, 2015). A recent study demonstrated that NA undergraduates with higher levels of EI had a greater likelihood to associate ambiguous mistreatment to racism (Delafield, 2022).…”
Section: Na Ei and College Outcomesmentioning
confidence: 99%